Current and Future Medical Treatment of Adenomyosis. Issue 4 (October 2016) - Tosti, Claudia; Troìa, Libera; Vannuccini, Silvia; Lazzeri, Lucia; Luisi, Stefano; Petraglia, Felice
Adenomyosis is a benign gynecological disorder associated with abnormal uterine bleeding, dysmenorrhea, dyspareunia and infertility, requiring a life-long management plan through medical or surgical treatment. The choice depends on woman's age, reproductive status and clinical symptoms. However, until now no drug labelled for adenomyosis is available; thus, the present review will focus on medical treatments currently used for adenomyosis and those in development. Adenomyosis may be considered a sex steroid hormone-related disorder associated with an intense inflammatory process. The use of gonadotropin-releasing hormone agonists (GnRH-a) for treating adenomyosis is described blocking the hypothalamic-pituitary-gonadal axis; however, it has long been associated with frequent and intolerable hypoestrogenic side effects. An antiproliferative effect of progestins suggests their use for treating adenomyosis, reducing bleeding and pain. Continuous oral norethisterone acetate or medroxyprogesterone acetate may help to inducing regression of adenomyosis, relief pain and reduce bleeding. The use of vaginal danazol has therapeutic effect on adenomyosis combining progestogenic and anti-inflammatory activity. The intrauterine device releasing levonorgestrel (Lng-IUD) is widely assessed in menorrhagia, and has been shown to be extremely effective in resolving pain and bleeding symptoms associated with adenomyosis. Recent data show a therapeutic effect of dienogest on adenomyosis symptoms. New drugs are under development for the treatment of adenomyosis, such as aromatase inhibitors (AIs) and selective estrogen receptor modulators (SERMs), that produce a hypoestrogenic environment reducing pain, but are correlated with some adverse effects and a recurrence of symptoms after discontinuation of treatment. Selective progesterone receptor modulators (SPRMs) may reduce adenomyosis-associated pelvic pain, by inhibiting endometrial proliferation and suppressing adenomyotic lesion growth, as shown in animal models; however, the long-term effect with SPRMs needs further determination.